Electrical analysis on implantation-related defect by nanoprobing methodology. (September 2016) - Chen, C.Q.; Ng, P.T.; Ang, G.B.; T an, H.; Rivai, Francis; Ma, Y.Z.; Ng, H.P.; Lam, Jeffery; Mai, Z.H.
Abstract: Implantation is the key process in the modern semiconductor process which forms the basic device cell by different doping ditribution, depth, angle and element type. They are the key factors to affect the transistor performance, but the implantation-related defect is invisible by the normal failure analysis method. Then electrical analysis and verification is necessary to visualize this kind of defect. Electrical theory is important in this kind of failure analysis to indirectly proven the problematic process. The transistor body effect is a well know effect which is utilized in some kind of IC design to change the transistor Vth for certain purpose. But nobody uses this effect for the implantation-related failure analysis since the implant itself is complex and is not ideally uniform as the theory model. In this paper, implantation-related defect was successfully identified by the application of transistor body effect combined with nanoprobing on the localized structure. Highlights: An implantation related invisible defect was analyzed. Body effect was employed for the experiment and electrical analysis. Semiconductor process was analyzed and correlated to the electrical result. Failure mechanism was plotted to successfully explain the failure mode.